Kidney Cancer Profile in National Cancer Center (NCC) - Dharmais Cancer Hospital - Diki Arma Duha; Edward Usfie Harahap; Rachmat Budi Santoso; Ikhlas Arief Bramono (National Cancer Center - Dharmais Cancer Hospital, 2022)
Background: Kidney cancer is one of the most prevalent cancers in urology. The higher prevalence of risk factors, as well as better diagnostic modalities, has led to a reported increase worldwide. The study aims to describe the profile and management pattern of kidney cancer patients at a tertiary referral center over seven years.Methods: A descriptive study was conducted to assess the profile and management of kidney patients in the national cancer center (NCC) - Dharmais Hospital Jakarta between January 2013 and December 2020. The variables collected included age, gender, stage (AJCC staging), histopathological result, and management, using the total sampling method.Results: A total of 53 kidney cancer cases were documented in NCC - Dharmais Hospital Jakarta from 2013 to 2020. Overall, males are more prevalent than females, with a sex ratio of 2.3:1. The most frequent age group was 51–65 years. The most common histological subtype was a clear cell in the renal cell carcinoma (RCC) subtype and sarcoma in the non-RCC subtype. Noticeably, end-stage (stage IV) was found in more than half of patients (65.6%), with no patient found in stage I. Radical nephrectomy was preferable to cytoreductive nephrectomy. Conclusions: : An increasing trend of kidney cancer incidence was found between 2013 and 2020 with most patients diagnosed with stage IV.